Prevention Children Sexual Abuse in Preschool with Picture Story Book - Dyah Rahmawatie Ratna Budi Utami; Erika Dewi Noorratri (P3M Universitas 'Aisyiyah Surakarta, 2021)
Background: Children sexual abuse (CSA) is a form of concern for parents and society, given the phenomenon that occurs is like an iceberg with an increasing prevalence every year. Parents play an important role in CSA prevention education, but the majority are confused about how to explain it. The picture book is expected to be a medium for educating parents to their children regarding the prevention of CSA in preschool children. Purpose: to produce a picture book as an effort to prevent KSA. Methods: This study used a research and development design. The development of this pictorial story book uses information from parents and teachers for initial data collection, while for product validation a team of experts consisting of material experts, media experts and linguists are used for product validation. Meanwhile, for the public test was 34 parents. The instruments used were interview guides and questionnaires. The data were analyzed qualitatively and quantitatively. Result: There is creation of ABIJAGARI a story book in the prevention of child sexual abuse that consist of 17 pages. Conclusion The picture story book entitled ABIJAGARI can be used as an alternative media in education on prevention of CSA